TANTANGAN ETIKA PROFESI GURU DALAM PENGUATAN KOMPETENSI KEPRIBADIAN DI ERA DISRUPSI DIGITAL - Dhipo Saputro, Ageng; Azzahra, Aliya; Maulana Firmansyah, Rizki; Muhlisin; Mafaakhir, Abul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The era of digital disruption has transformed systems and patterns of interaction in the world of education, but it has also raised serious challenges to teachers’ professional ethics, such as the blurring of professional boundaries on social media, a decline in students’ respect, and the rise in cases of ethical violations by educators in the digital space. This literature review aims to analyze the challenges to teachers’ professional ethics and identify strategies for strengthening personal competencies as the foundation of character education in the digital age. The research findings indicate that professional ethics and personal competencies are the main pillars of successful character education for students. Teachers who possess moral integrity, emotional stability, exemplary conduct, and consistency between words and actions both in the real world and the digital realm are capable of serving as ethical role models for students. Conversely, neglecting ethics, particularly on social media, has the potential to cause moral confusion and a crisis of trust. Continuous professional development must include strengthening professional ethics, moral reflection, emotional management, and exemplary behavior in the digital space, not just a focus on technical skills. Synergy is needed between teachers, schools, and policymakers to create a character-based recruitment system, digital ethics training, and holistic supervision of teacher behavior. Without a strengthening of professional ethics that is integrated with the challenges of the digital age, the use of technology in education will lose its essence and trigger a moral crisis among the younger generation.